Comparison of the perioperative efficacy between single-port and two-port video-assisted thoracoscopic surgery anatomical lung resection for non-small cell lung cancer: a systematic review and meta-analysis - Yang, Wenlong; Zhang, Guozhong; Pan, Shu; Wang, Zhihao; Li, Jianfeng; Ren, Weidong; Shi, Hongcan (Journal of Thoracic Disease, 2019)
Background: With the development of novel surgical techniques and instruments over the recent years, more and more surgeons consider single-port video-assisted thoracoscopic surgery (VATS) as a feasible option. However, whether single-port thoracoscopic surgery has more potential advantages than two-port thoracoscopic surgery for non-small cell lung cancer remains unknown. We conducted this systematic review and meta-analysis to compare the perioperative efficacy between single-port and two-port VATS anatomical lung resection for non-small cell lung cancer (NSCLC). Methods: Eleven studies were identified from the databases of The Cochrane Library, PubMed, Embase, Web of science, and China Biology Medicine disc (CBMdisc). Prospective studies and retrospective studies that evaluated the perioperative efficacy of single-port VATS compared with two-port VATS were analyzed. We used 95% confidence intervals (CIs) to calculate the odds ratio (OR), and the weight mean difference (WMD). Results: A total of 11 studies (3 prospective studies and 8 retrospective studies), including 1,592 patients, were included. We found that the duration of the operation in single-port VATS anatomical lung resection for NSCLC was shorter (P=0.02). Also, the bleeding volume amount was lower (P=0.01), the length of postoperative drainage was shorter (P